Insertion of fullerene layer for bulk heterojunction organic photovoltaic cell fabricated by electrospray deposition method. Issue 12 (7th October 2013) - Fukuda, Takeshi; Takagi, Kenji; Liao, Yingjie
Abstract An improved power conversion efficiency (PCE) of bulk heterojunction organic photovoltaic cell (OPV) was achieved by inserting an n‐type [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) layer between the active layer and a metal electrode. The controlled substrate temperature was found to be a useful parameter for the multilayer structure (active layer/ PCBM) by the electrospray deposition method. Under optimized substrate temperature during the PCBM deposition, a multilayer structure could be formed, and the PCE was improved up to 1.94%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)